Thoracic complications of hydatic cysts of the liver dome - Delbene, Roberto (Cirugía del Uruguay, 2003)
This report refers to a surgical procedure documented by video of 2 patients with hydatid cysts (HC) in post-superior segments of right liver, with thoracic complications. One of them was firmly adhered to diaphragm and the other with hepatopulmonary transit.